Application of a life cycle assessment for assessing municipal solid waste management systems in Bolivia in an international cooperative framework - Ferronato, Navarro (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2020)
Using a life cycle assessment (LCA) to evaluate municipal solid waste management (MSWM) systems is strongly recommended and the approach has been used in high-income contexts. However, stakeholders in low to middle income countries are not aware of the potential of this approach, mainly due to a lack of financial resources and technical ability. The present work introduces a LCA of MSWM system scenarios into a developing city using an academic licence for the LCA software that is available for use exclusively by researchers. The MSWM system in place in 2018 in La Paz (Bolivia) was assessed according to seven scenarios. The novelty of the research is twofold: the use of LCA academic licensing in a low to middle income region where LCA is unknown as planning tool; and discussing the potential of the approach in conjunction with local and international stakeholders with a view to starting MSWM projects. The results of the analysis allow for the consideration of energy recovery and materials recycling as the main methods by which the environmental impact of MSW can be reduced, as has also been reported by other LCA studies conducted with full licensing of the relevant software. Moreover, the research is the basis for cooperative development projects that will adopt the LCA approach as the main assessment tool. The study discusses the importance of cooperation between universities and local governments for implementing new strategies for MSWM assessment and planning. The research is a contribution towards improving technical knowledge in developing countries for boosting sustainable development